Validating a human biotelemetry system for use in captive blue wildebeest (Connochaetes taurinus). Issue 4 (17th May 2015) - Laubscher, Liesel L.; Hoffman, Louwrens C.; Pitts, Neville I.; Raath, Jacobus P.
<x xml:space="preserve">Abstract</x> We fitted two blue wildebeest (Connochaetes taurinus) with modified versions of the Equivital™ EQ02 wireless monitoring system to evaluate if the device could accurately measure heart rate and respiration rate in this species whilst anaesthetized as well as whilst fully conscious in captivity. Whilst under anaesthesia, we monitored each animal's heart rate and respiration rate using the Equivital™ biotelemetry belt, a Cardell® veterinary monitor and manual measurements. The animals were also administered doxapram hydrochloride (Dopram®) and adrenaline intravenously at different times to stimulate changes in respiration and heart rate, respectively. Once 30 minutes of monitoring was completed, we reversed the anaesthetic and left the animals in captivity for 24 hours whilst wearing the Equivital™ belts. After 24 hr, we repeated the anaesthesia and monitoring as well as the administration of the doxapram hydrochloride and adrenaline. Intraclass Correlation Coefficients (ICC) calculated between all three monitoring methods showed moderate to excellent agreements for heart rate on both days (ICC: 0.73–0.98). ICCs calculated between the three methods for respiration rate showed good to excellent agreement between the Equivital belt and the other two methods (0.82–0.92) with the exception of occasions when only poor to fair agreements were found between the Cardell® measurements and manual measurements. Heart rate and respiration rate were also found to increase with motion while animals were in captivity. The results indicate that a modified version of the Equivital™ EQ02 system can be used as a potential biotelemetry device for measuring heart and respiration rate in captive blue wildebeest. Zoo Biol. 34:321–327, 2015. © 2015 Wiley Periodicals Inc.